COVID-19 and marine fishers in India: livelihood implications and coping strategies - A Suresh,; V K Sajesh,; R Raghu Prakash,; A K Mohanty,; L N Murthy,; A K Jha,; C N Ravishankar, (Agricultural Economics Research Review, 2023)
The paper examines the livelihood impacts of COVID-19 on marine capture fishers in India, the coping mechanisms adopted by them, and their correlates, by using primary data collected from fishers of Andhra Pradesh on the eastern coast and Kerala on the western coast. The fishers adopted several coping strategies, correlated with personal attributes, ownership of economic assets, social capital, and economic status. The study advocates the need to carefully evaluate the trade-off between restrictions to contain COVID-19 and loss of livelihood.